Approach and Development of a University Studies Itinerary Aimed to People with Intellectual Disability: Structure and Results of its Implementation - Ricardo Moreno-Rodríguez; Nerea Felgueras Custodio; Miriam Díaz Vega (Universidad Autónoma de Madrid, 2019)
This research aims to address the impact of the training proposal on both the student himself and the university community. The design of this research presents a mixed approach, focusing on fieldwork. The collection of information was carried out through direct observation and, on the other hand, by administering questionnaires that assess the impact of training on both the students as in the university community. This training found to increase the chances of finding a job, as well as keeping it in time thanks to specific training and training in basic social, emotional and pre-work skills. The results also show a high level of satisfaction in teachers and speakers who participated in the training. The implementation of these programs is necessary to address the academic and employment situation of young people with intellectual disabilities. Likewise, the involvement and collaboration of the university community is a determining factor in providing a quality and equal opportunities.